Integrated Decision Support System? DONUT-Prospect - Eduardo Castro; Jo\~ao Marques; Paulo Batista; Monique Borges (European Regional Science Association (ERSA), 2014)
The socioeconomic importance of housing and its medium- and long-term investment returns requires a significant effort to predict future dynamics to ensure that the different real estate market agents make the best decisions. Furthermore, the territory structure and the lack of information and transparency of the housing market mechanisms also influence its understanding. There is a variety of literature, in the field of spatial economics that gives theoretical basis for predict housing prices and attributes valuation. However, these analytical models are subject to criticisms because of their inability to integrate the variability of exogenous factors. Therefore, predictions of housing prices and attributes valuation may be affected by not considering the spatial and temporal evolution. Foresight analysis, which will be the main focus of this paper, can be considered as a complementary and useful tool to these analytical models. The paper presents an Integrated Decision Support System? DONUT-Prospect, designed as a decision making framework that combines technically informed subjectivity (foresight analysis) with more rigorous models (econometric models). This empirical application has been developed in the context of a local housing market (Aveiro ? Ílhavo municipalities), providing outcomes about the evolution of social and economic phenomena, as well as the heterogeneity of both supply and demand side: the former regarding housing prices and features; and the latter considering the type of consumers. An important result of this exercise is the estimation of housing characteristics and its hedonic prices in 2030, i.e., a picture of the housing market in 2030. In short, DONUT-Prospect presents a way to combine two main foresight techniques (scenario analysis and Delphi surveys) with a traditional hedonic housing price model. The methodology is supported on the assumption that it is possible: i) to discuss strategies in the context of great uncertainty; and ii) to identify trends and assess future evolution. The work is organized in 3 parts: i) description of the structure of DONUT-prospect; ii) presentation of how each foresight technique was implemented in the context of the integrated model; and iii) main outputs and result discussion. The main results show that DONUT-Prospect will be especially useful in generating consensus between different real estate market agents. This will be true when the traditional communication channels are weak and strongly conditioned by the lack of public available information and transparency of the housing market mechanisms.
Keywords: R31; D81; R20; 330; housing market; decision support system; foresight